Sociolinguistic centrifuge comparing language attitudes form urban center to urban periphery - Estipona, Michael Ian Benedict P. (Philippine Journal of Linguistics, 2009)
Much research on L2 learning and use plays a role in principled and reasoned language planning, and even relevant and pivotal legislation as seen in the tug-of-war between Filipino and English as medium of instruction that has been a national issue for decades. This study builds on the comparatively-emergent language attitudes-based research done in the Philippines, comparing language attitudes of Ateneo de Manila University college undergraduate students with those from Romblon State College. While not necessarily reflective of the attitudes of their larger populations, both respondent sets see both languages as important and useful languages for education, entertainment, and employment; English, while the preferred MOl, does no necessarily carry higher apparent social status. On the whole, integrative and instrumental motivations for using either language still make both of them vital and generally favored options for learners and users close to and far from the urban center.